Urgensitas Semantik Dalam Memahami Kandungan Al-Qur’an - Rajul Kahfi, Muhammad; Ahmadi, Ahmadi (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
The Qur'an as a way of life deserves to be studied and understood. One way to understand the Qur'an is through interpretation. One of them uses semantic methods. The uniqueness of the semantic method is that it focuses more on the meaning of the word verse which results in a more detailed interpretation, so the urgency of this method needs to be taken into account. This study analyzes the concept of semantics, types, and their application in interpretation. The method used in this study is a literature study by exploring various sources such as books and journal articles. The results of this study indicate that Semantics is a language analysis method used in the interpretation of the Qur'an by focusing on the meaning of words from a verse. Semantics consists of various types of